Immunophenotyping and efficacy of low dose ATG in non-sensitized kidney recipients undergoing early steroid withdrawal: a randomized pilot study. - Monica Grafals; Brian Smith; Naoka Murakami; Agnes Trabucco; Katherine Hamill; Erick Marangos; Hannah Gilligan; Elizabeth A Pomfret; James J Pomposelli; Mary A Simpson; Jamil Azzi; Nader Najafian; et al. (PLoS ONE, 2014)
Rabbit antithymocyte globulin (ATG) is commonly used as an induction therapy in renal transplant recipients, but the ideal dosage in tacrolimus-based early steroid withdrawal protocols has not been established. The purpose of this pilot study was to determine the immunophenotyping and efficacy of lower dose ATG in low immunological-risk kidney transplant recipients. In this prospective study, 45 patients were randomized (1∶1) to our standard dose ATG (total dose 3.75 mg/kg)(sATG) vs. lower dose 2.25 mg/kg (lowATG). All patients underwent early steroid withdrawal within 7 days. The primary end point was biopsy-proven acute rejection at 12 months. Prospective immunophenotyping of freshly isolated PBMCs was performed at baseline, 3, 6, 12 months post-transplant. The rate of acute rejection was 17% and 10% in the sATG and lowATG, respectively. Effector memory T cells, Tregs and recent thymic emigrants T cells had similar kinetics post-transplant in both groups. No statistically significant differences were found in graft survival, patient survival or infections between the two groups, though there was a non-significant increase in leukopenia (43%v s. 30%), CMV (8% vs. 0) and BK (4% vs. 0) infections in sATG group vs. lowATG. In sum, in low immunological risk kidney recipients undergoing steroid withdrawal, low dose ATG seems to be efficacious in preventing acute rejection and depleting T cells with potentially lower infectious complications. A larger study is warranted to confirm these findings.ClinicalTrials.gov NCT00548405.